Strong Coupling, Hyperbolic Metamaterials and Optical Tamm States in Layered Dielectric-Plasmonic Media - Gonçalves, Manuel Rodrigues (Frontiers in Nanotechnology, 2021)
Thin films of noble metals with thickness smaller than the wavelength of light constitute one of the most investigated structures in plasmonics. The fact that surface plasmon modes can be excited in these films by different ways and the simplicity of fabrication offer ideal conditions for applications in nanophotonics. The generation of optical modes in coupled Fabry-Pérot planar cavities and their migration to hyperbolic metamaterials is investigated. Coupled Fabry-Pérot cavities behave as simple coupled resonators. When the intra-cavity media have different refractive indices in two or more coupled cavities resonance anti-crossings arise. The application of this kind of strong coupling in sensing is foreseen. Beyond the cavity modes excited by propagating waves, also long range plasmonic guided modes can be excited using emitters or evanescent waves. A periodic structure made by multiple plasmonic films and dielectrica supports bulk plasmons, of large propagation constant and increasing field amplitude. The optical response of these structures approaches that of the hyperbolic metamaterial predicted by the effective medium theory. Light can propagate with full transmission in a structure made of a photonic crystal based on quarter wavelength layers and a second photonic crystal with an overlapping forbidden band, but presenting a non-trivial topological phase achieved by band inversion. This is due to excitation of optical Tamm states at the boundary between both crystals. The extension to multiple optical Tamm states using dielectric and plasmonic materials and the symmetries of the edge states is investigated.